Light intensity physical activity increases and sedentary behavior decreases following total knee arthroplasty in patients with osteoarthritis - Frimpong, E.; McVeigh, Joanne; van der Jagt, D.; Mokete, L.; Kaoje, Y.; Tikly, M.; Meiring, R. (Springer, 2018)
© 2018 European Society of Sports Traumatology, Knee Surgery, Arthroscopy (ESSKA) Purpose: To describe objectively measured changes in the volume and pattern of physical activity and sedentary behavior in patients undergoing total knee arthroplasty for osteoarthritis. Methods: Physical activity and sedentary behavior were measured in patients (13 males, 76 females) with a mean age of 64 years (range 55–80) and end-stage osteoarthritis of the knee, using an accelerometer (ActiGraph GT3X+) for seven consecutive days (24 h/day) prior to, 6 weeks and 6 months after total knee arthroplasty. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), University of California Los Angeles (UCLA) Activity index and range of motion (ROM) were also assessed. Results: Proportion of time spent in sedentary behavior decreased from baseline to 6 months (mean 70.1 vs. 64.0%; p = 0.009) and the interruptions to sedentary behavior improved between baseline and 6 months after total knee arthroplasty (mean 85.0–93.0 breaks/day, p = 0.014). Proportion of time spent in light physical activity increased from baseline to 6 months after total knee arthroplasty (29.0 vs. 34.8%; p = 0.008). There was no change in time spent in moderate to vigorous physical activity after total knee arthroplasty. WOMAC (median 71.0 vs. 4.0, p < 0.001), UCLA (median 2.0 vs. 5.0, p < 0.001) as well as ROM [median (0.0°–90.0°) vs. (0.0°–110°), p < 0.05] scores improved between baseline and 6 months after total knee arthroplasty. Conclusion: Clinically, functional improvements in patients following total knee arthroplasty may be assessed by objectively measuring changes in low intensity activity behaviors. The use of accelerometers in this study gives new insights into activity accumulation patterns in a clinical population and highlights their use in determining a behavioral response to an intervention. Level of evidence: II.